LARUNG DAN KEKUATAN PENGALAMAN YANG ADA DI DALAMNYA - Katrini, Yulia Esti (Majalah Transformatika, 2009)
Literatury work is created by the autherthrough contemplation, it means it is not created through blank idea. It can be said that literary work is created through yhe combination of knowledge of the author and his soul experience as the feflections of real human life novel